Modern weapons and military equipment for issue 4/2013 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Multirole fighter MiG-29M/M2 renamed into MiG-35/D; Textron to develop new strike and reconnaissance jet; Boeing and Saab regarding possibility of offering Gripen for USAF new T-X program; Training version of Russian Mi-28 attack helicopter presented; German Eurofighters to get air-to-ground capabilities in 2017; Missile Air Defence System S-350 Vitjaz prototype revealed; Polish Air Force receives first upgraded MiG-29 fighters; Argentine IA-63 Pampa III trainers go into production; Chinese UCAV ready for flight tests; Helicopter Mi-8SMB set new altitude record; Maiden flight of HÜRKUŞ Turkish-made trainer